New global frontiers in regulation: the age of nanotechnology (Cheltenham, 2007)
"Our growing ability to manufacture materials at the atomic scale will change our lives for the better, and tomorrow's nano-economy will outperform today's information age. Or so its proponents claim. Others maintain that a future dominated by commercial incentives risks a toxicological nightmare to rival the sorry global story of asbestos.This important volume is a timely contribution to increasing international calls to regulate nanotechnologies. By investigating the ways in which we could regulate these advances, and what we are learning from regulating existing biotechnologies and information technologies, the book debates the roles of government, business actors and the professions in protecting and enhancing the lives of citizens. In placing particular emphasis on the lessons of earlier technology advances, this study is unique in its broad consideration of the ethical, legal and social issues entwined within the development of the nanotechnology family. The multi-jurisdictional and interdisciplinary nature of the book will appeal to governments, academics, and civil societies across many parts of the world, whilst also remaining accessible to informed readers with an interest in nanotechnology and the policy and governance issues associated with technology development and regulation."